Microsoft Excel 2010 : - O'Leary, Timothy J. (McGraw-Hill, 2011)
Timothy and Linda O'Leary and the Computer Information Technology Team at McGraw-Hill Higher Education offer your students a fully integrated learning program with time-tested quality and reliability. Office 2010: A Case Approach offers running case study throughout the text to help students understand the material in a consistent, relevant environment